Agent Communication for Schedulling in the Extended Enterprise, Infrastructures for Virtual Enterprises - Reis, J.; Mamede, N.; O'Neill, Henrique (IFIP TC5 WG5.3/PRODNET Working Conference on Infrastructures for Virtual Enterprises (PRO-VE'99), 1999)
In previous work we have proposed how to model enterprise facilities (like factories, warehouses, etc.) in a multi product production/distribution network, capacity management at those facilities, and agents which act as enterprise managers, taking decisions that affect the available capacity. In this article we describe a model for the internal activities of an agent for communication for multi-agent coordination in task scheduling in an integrated logistics environment.